2006
DOI: 10.1111/j.1365-2486.2006.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Anuran abundance and persistence in agricultural landscapes during a climatic extreme

Abstract: Climate change in concert with habitat loss and degradation are major threats to global biodiversity. As part of climate change, the occurrence of extreme climatic events is expected to increase. Agricultural intensification has led to the increased homogeneity of agricultural habitats and declines in farmland species diversity. We investigated the abundance of common frog Rana temporaria populations in boreal farmlands in relation to multiple scales of landscape structure during years 2002-2003, and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 84 publications
(104 reference statements)
2
51
0
Order By: Relevance
“…Study periods of several years also enable to investigate if and how populations recover. Other studies merely assessed the period immediately following the extreme weather event (Mouthon and Daufresne 2006;Piha et al 2007). Therefore, they only pointed towards declining populations and changes in community composition, but did not give any indications about the reversibility of these effects.…”
Section: Some Implications For Management and Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Study periods of several years also enable to investigate if and how populations recover. Other studies merely assessed the period immediately following the extreme weather event (Mouthon and Daufresne 2006;Piha et al 2007). Therefore, they only pointed towards declining populations and changes in community composition, but did not give any indications about the reversibility of these effects.…”
Section: Some Implications For Management and Conservationmentioning
confidence: 99%
“…Because climate change models predict an increased occurrence of extreme weather events during the second half of the twenty-first century (Trenberth et al 2007;Meehl and Tebaldi 2004), it is important to know how species react to extreme climatic events (McLaughlin et al 2002). Up till now, most research on the effects of climate change has primarily focused on the consequences of increased average temperatures, whereas studies on the effects of extreme events are scarce (Opdam and Wascher 2004, but see Mouthon and Daufresne 2006;Piha et al 2007;Rouault et al 2006;Jentsch et al 2007). Research on the combined effects of these extreme events and habitat fragmentation are even more scarce (Opdam and Wascher 2004), although modelling studies have shown the combination of habitat loss and climate change to be a disastrous mixture (Travis 2003;Thomas et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Central America, amphibian declines have been connected with climate-driven reductions in leaf-litter microhabitat (Whitfield et al 2007), while in Europe, amphibian persistence during a climate extreme was related to landscape heterogeneity (Piha et al 2007). Understanding the spatial scale at which climate-associated threats affect amphibians is crucial for developing and effectively implementing management responses.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that landscape heterogeneity confers stability to landscapes and may buffer populations against environmental change, relative to organisms in landscapes that are more homogeneous (Benton et al 2003;Dover and Settele 2009;Forman 1997;Luoto and Heikkinen 2008). Support for this hypothesis has been demonstrated experimentally for crickets (Kindvall 1996), amphibians (Piha et al 2007), and butterflies (Oliver et al 2010). Avian populations in parts of the Western US have contended with natural heterogeneity for thousands of years and may be less affected by fragmentation processes, such as exurban development, than avian populations of the relatively more homogeneous landscapes of the pre-European-settlement Eastern US (George and Dobkin 2002;Tewksbury et al 1998).…”
Section: Introductionmentioning
confidence: 86%